Toward an Integrated ASEAN Labor Market Prospects and Challenges for CLMV Countries - Nguyen, Huy Hoàng (Đại học Kinh tế, 2016)
In this context, this paper aims to focus on resolving the following two main questions. The first is What is the content of the ASEAN commitments for promoting an Integrated ASEAN Labor Market and the ASEAN Labor Ministers Meeting would be a more complete market for free movement of skilled and professional labor within ASEAN countries?. The second is What are the prospects and challenges for CLMV countries?It is important to note here that in this paper, we focus only on a theoretical analysis of the integrated labor market in ASEAN and prospects as well as challenges for CLMV countries. Thus, the paper just provides theoretically analytical information and outcomes of the proposed research.